Experimental Data and New Binary Interaction Parameters for Ethanol- Water VLE at Low Pressures Using NRTL and UNIQUAC - Guevara Luna, Marco Andrés; Guevara Luna, Fredy Alejandro; Belalcázar Cerón, Luis Carlos (TECCIENCIA, 2018)
Ethanol is currently one of the most important and attractive sources of energy with a heating value of 12800 kJ/kg. Ethanol is commonly obtained from many sources worldwide, mainly renewable sources, and its separation is achieved typically by atmospheric distillation. Even so, there is new technologies looking for cheaper and more efficient ethanol separation and purification: pressure-swing distillation, extractive distillation, adsorption with molecular sieves and vacuum membrane distillation. The design, rating and optimization of these process technologies requires a reliable and universal thermodynamic modeling approach capable of represents the ethanol-water system properties, and in particular the vapor-liquid equilibrium (VLE) near the azeotropic point. This study summarize VLE experimental data for ethanol-water system at 3 vacuum pressures (13.15, 19.71 and 101.32 kPa), and 17 azeotropic point data. Thermodynamic consistency test of the data was performed using the Redlich-Kister method. The parameters and constants for the detailed thermodynamic modeling of the ethanol-water system using polar fluid Soave-Redlich-Kwong equation of state (polar-SRK) are summarized as part of this study, as well as the standard binary interaction parameters for NRTL and UNIQUAC excess Gibbs energy models. Both models are used simultaneously for the simulations involved in the chemical process engineering activities in science, academy and industry. The main target of this study consist in the regression of new binary interaction parameters in a temperature dependent form compatible with the most process simulation software, for NRTL and UNIQUAC, and its validation using experimental data for azeotropic points at 3 different low pressures with errors of less than 1%, for temperature and ethanol molar fraction in the vapor phase. The regressed new parameters were tested using isobaric experimental data for VLE at the 3 under-atmospheric pressures mentioned, obtaining correlation coefficient (R2) values of about 1. The calculations were performed using Python 3.4® codes developed and supplied by S&S and Aspen properties® V8.6 provided by the Universidad Nacional de Colombia.